(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Grudhrasi as mentioned in Ayurveda explains a disorder where in pain starts from Sphik Pradesha and radiates downwards to Kati, Prusta, Uru, Janu, Jangha and the patient is unable to walk properly. The case reported here showed similar features that of lumbar vertebral disc prolapsed. After following a specific treatment protocol of Ayurvedic treatments, significant regression in the condition was observed and patient could completely stop the use of analgesics and anti-inflammatory drugs which were used by the patient priory. A 32 year old male, presented with complains of severe low back ache radiating to left lower limb and inability to walk since 15 days. On the basis of symptoms, thorough examination and evidence of imaging technique, the case was diagnosed as Grudrasi. A specific treatment protocol of Ayurvedic procedures were followed after thorough examination of the patient. The pain completely resolved and patient was able to walk without support. Photographs of the patient were captured before and after the treatment for records. The outcome was a combined effect of Shamana and Shodhana Chikitsa as well as Yogasanas. The scope of a new treatment protocol is discussed in this paper which can give a considerable relief to those patients suffering from Grudrasi.